2019
DOI: 10.1097/brs.0000000000003054
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Type I Diabetes in Intervertebral Disc Degeneration

Abstract: Study Design. An experimental laboratory study. Objective. To investigate the pathogenesis of intervertebral disc degeneration (IDD) in a murine model of type 1 diabetes mellitus (DM), namely nonobese diabetic (NOD) mouse. Summary of Background Data. IDD is a leading contributor of low back pain, which represents one of the most disabling symptoms within the adult population. DM is a chronic metabolic diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Osteocalcin is a bone-derived hormone-like protein. It could favor physiological functions increasing the bone formation [57], regulating the muscle decrease related to age [58], and reducing the risk of diabetes type II [4,59]. Chahla et al [60] reported in their study that osteocalcin is higher in patients who perform regular PA, with an increase in bone mineralization, muscle function, and reduction of risk of diabetes type II.…”
Section: Discussionmentioning
confidence: 99%
“…Osteocalcin is a bone-derived hormone-like protein. It could favor physiological functions increasing the bone formation [57], regulating the muscle decrease related to age [58], and reducing the risk of diabetes type II [4,59]. Chahla et al [60] reported in their study that osteocalcin is higher in patients who perform regular PA, with an increase in bone mineralization, muscle function, and reduction of risk of diabetes type II.…”
Section: Discussionmentioning
confidence: 99%
“…The physical fitness term, refers to a series of attributes that can be achieved by training, such as endurance and strength, abilities that are closely related to PA [ 5 ]. However, PA in overweight or obese individuals with diabetes often represents an insurmountable problem since these subjects suffer of several musculoskeletal disorders such as osteoarthritis [ 10 ], chronic low back pain due to intervertebral disc degeneration [ 11 ], and other musculoskeletal disorders [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the AGE-RAGE signaling pathway in diabetic polyneuropathy, a complication of diabetes, is commonly observed, and increased AGE-RAGE signaling exacerbates degenerative disorders of peripheral neurons (90). In fact, a recent study reported no significant difference in the GAG content or histological features between discs from non-obese diabetic mice and euglycemic littermates, but noted increases in cellular apoptosis and matrix aggrecan fragmentation (91). To determine the link between diabetes and IDD, the role of the AGE-RAGE signaling pathway in IDD requires further research.…”
Section: Differentially Regulated Proteins and Their Signaling Pathwamentioning
confidence: 99%